Case report: dual diagnosis of Mulibrey nanism and Jacobs syndrome in an Indian boy - Pritti Kumari; Rohina Aggarwal; Akshi Valodara; Hetvi Patel; Dipak Dhoriya; Ankita Suthar; Somesh Aggarwal (Egyptian Journal of Medical Human Genetics)
Abstract Background Mulibrey-Nanism (Muscle-liver-brain-eye Nanism = dwarfism; MUL) is a rare genetic syndrome caused by TRIM37 gene variants characterized by growth failure, dysmorphic features and congestive heart failure. We report a 6-year-old boy with Mulibrey nanism and Jacobs syndrome who was referred to us on suspicion of some genetic syndrome. Case description A 6-year-old boy was referred for genetic evaluation with a suspected diagnosis of Silver-Russell syndrome. Comprehensive genetic analysis of the proband was conducted using both classical and modern techniques, including karyotyping, chromosomal microarray (CMA), and whole exome sequencing (WES). G-banding chromosomal analysis revealed a mosaic pattern of 47,XYY[25]/46,XY[25], indicative of Jacobs syndrome. Further analysis with CMA identified a pathogenic mosaic gain of Y chromosome consistent with the karyotype results; no other pathogenic copy number variants were observed. Finally, WES revealed a nonsense homozygous variant c.586C > T in the TRIM37 gene which is causative of Mulibrey nanism. Conclusion This case marks the first documented instance in India of the co-occurrence of Mulibrey nanism and Jacobs syndrome, adding significant insights into the genetic diversity and clinical presentation of these conditions. The study highlights the importance of various genetic tests to diagnose rare genetic syndromes with overlapping phenotype.